Penerapan Komunikasi Interpersonal pada Media Sosial : SMK N 1 Babelan Kabupaten Bekasi Jawa Barat - Muria Putriana; Wina Puspitasari; Asep Sugiarto; Yuni A. Muharam; Tj. Darmawan (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study aims to provide an understanding of the application of interpersonal communication through social media in a vocational high school environment, namely at SMK Negeri 1 Babelan, Bekasi Regency, West Java. The implementation steps given to SMK Negeri 1 Babelan, Bekasi Regency, are related to an aware understanding of media law to prevent the negative effects of social media, especially considering the current condition of the younger generation who are very active on social media, they must be equipped with knowledge of understanding content which can lead to social legal sanctions. to be wiser in using social media at an early age. The qualitative method is descriptive. Data was collected through observation, interviews, discussion forums and documentation. While the data analysis technique is presented in the form of narrative text through procedures namely coding, data reduction, data presentation, data triangulation, drawing conclusions and data analysis. The results show that the steps for implementing interpersonal communication are very comprehensive to help students and teachers of SMK Negeri 1 Babelan understand the importance of ethics in communicating online, especially when having to carry out activities with students online. Many teachers and students at SMK N 1 Babelan are active on various social media platforms so it is important for teachers and students to understand how to communicate properly and effectively. Poor communication on social media can negatively affect the image and reputation of a teacher, school or institution. As for the implications that need to be carried out related to understanding the law so that understanding about legal awareness of media is very important to prevent, the negative impact of social media is even greater when there is a lack of knowledge about understanding content which can lead to legal sanctions for the students themselves or the social environment.